2013
DOI: 10.1108/jgm-01-2013-0006
|View full text |Cite
|
Sign up to set email alerts
|

Foreign executives in local organisations

Abstract: Purpose – The purpose of this paper is to investigate foreign executives appointed into cultural contexts distant from their country of origin and headquarters of organisations to which host-country nationals (HCNs) they supervise and HCN superiors they report to attribute a “local” national identity. Significant differences of these foreign executives in local organisations (FELOs) from other forms of expatriation, including assigned and self-initiated expatriates, are identified and discussed. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 50 publications
(67 reference statements)
0
29
0
Order By: Relevance
“…However, despite the recent increase in numbers of SIE studies in cross‐cultural career contexts (e.g. Arp, Hutchings and Smith ; Isakovic, bin Mohammed and Whitman ; Makkonen , b; Muir, Wallace and McMurray ; Rodriguez and Scurry ; Von Borell de Araujo et al. ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, despite the recent increase in numbers of SIE studies in cross‐cultural career contexts (e.g. Arp, Hutchings and Smith ; Isakovic, bin Mohammed and Whitman ; Makkonen , b; Muir, Wallace and McMurray ; Rodriguez and Scurry ; Von Borell de Araujo et al. ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on FELOs has shown that both the foreign individuals and their host-country colleagues involved in this phenomenon view their workplaces as significantly different from expatriate assignments of global multinationals. Most important, local executives in this research do not describe their own companies as "global multinationals" under the inpatriation paradigm (Arp, 2012;Arp, Hutchings, & Smith, 2011, 2012. Overall, the FELO phenomenon can be viewed as part of the broader research paradigms of "boundary-less careers" (Bird, 1994;Stahl, Miller, & Tung, 2002) and "selfinitiated expatriation" (Jokinen, Brewster, & Suutari, 2008;Suutari & Brewster, 2000), which have in recent years captured the interest of international management scholars.…”
Section: Felos Vs Other Workplace Phenomenamentioning
confidence: 88%
“…These and other points of distinction are prominently mentioned by participants of in-depth interview studies (e.g. Arp, forthcoming 2013;Arp et al, 2011), highlighting that FELOs as well as their local peers perceive these workplaces to be quite different from other forms of expatriation. In addition, research with these two groups of executives illustrates that the reasons why foreign executives are initially appointed in spite of significant cultural distance, what they contribute to the local organisations that they work for, why some of them remain in their positions, and why these positions are not filled with local executives (Arp, forthcoming 2013), have little to do with the reasons for traditional expatriate assignments (i.e.…”
Section: Introductionmentioning
confidence: 96%
“…The Korn/Ferry Institute, 2009). While these foreign executives in local organisations (FELOs) can probably best be viewed as a specific form of self-initiated expatriation (SIE), their workplaces differ significantly from typical expatriate assignments (Arp, Hutchings, & Smith, 2011, forthcoming 2013.…”
Section: Introductionmentioning
confidence: 99%